Using the Technology Acceptance Model to Analyze Information System Performance - Kristianto Purwoko Widodo; Anisa Rachmawati; Lilis Endang WIjayanti (Universitas Teknologi Yogyakarta, 2022)
This article analyzes user perceptions of information systems. The DIY provincial government agency conducted the research. The analysis is based on the Technology Acceptance Model (TAM). Information system performance is associated with perceived usefulness (POU) and perceived ease of use (PEU). Based on the technology acceptance model, the user will be able to accept the information system if the user's information system has a perception that the information system is helpful for the user and easy to use. This article analyzes whether user perceptions of the usefulness and ease of use of information systems affect user perceptions of information system performance. The study was conducted on SIPKD users in the DIY provincial government. The regional financial management information system is one of the systems used by the DIY provincial government. SIPKD is a system that all local government work units must use. SIPKD operators are appointed with a regional head decree. The research data was obtained by distributing questionnaires to 100 SIPKD operators. Data were analyzed by moderating regression analysis. Data processing results show that POU and PEU affect user perceptions of information system performance. The proven task complexity variable serves as a moderating variable between POU and PEU with information system performance.